Glamour: Famous Gowns of the Silver Screen, curated by Cornelia Bujin, Italo Nunziata and Hannu Palosuo. Issue 2 (1st December 2021) - Ovtchinnikova, Alexandra; Kalmakurki, Maarit
Glamour: Famous Gowns of the Silver Screen, curated by Cornelia Bujin, Italo Nunziata and Hannu PalosuoSerlachius Museum Gustaf, Mänttä, 26 September 2020‐10 January 2021